2022
DOI: 10.15252/emmm.202114526
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and enhancing migration of human myogenic progenitors using directed iPS cell differentiation and advanced tissue modelling

Abstract: Muscle satellite stem cells (MuSCs) are responsible for skeletal muscle growth and regeneration. Despite their differentiation potential, human MuSCs have limited in vitro expansion and in vivo migration capacity, limiting their use in cell therapies for diseases affecting multiple skeletal muscles. Several protocols have been developed to derive MuSC-like progenitors from human induced pluripotent stem (iPS) cells (hiPSCs) to establish a source of myogenic cells with controllable proliferation and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…We then assessed if the editing strategy would induce utrophin upregulation and correct sarcolemma localization in a model more closely resembling skeletal muscle tissue architecture than conventional monolayer cultures (65). To this aim, we generated 3D engineered skeletal muscles by culturing Cas9 only or Cas9/gRNA treated hDMD myoblasts in our established 3D platform capable to model muscular dystrophies and therapeutic interventions, including the possibility to study muscle function (65)(66)(67)(68)(69). 8 days after treatment, edited and control hDMD myoblasts were differentiated into a 3D hydrogel as previously described (69) (Fig 4A ; Fig S3A-B).…”
Section: Disruption Of Let-7c Bs Results In Utrophin Upregulation In ...mentioning
confidence: 99%
“…We then assessed if the editing strategy would induce utrophin upregulation and correct sarcolemma localization in a model more closely resembling skeletal muscle tissue architecture than conventional monolayer cultures (65). To this aim, we generated 3D engineered skeletal muscles by culturing Cas9 only or Cas9/gRNA treated hDMD myoblasts in our established 3D platform capable to model muscular dystrophies and therapeutic interventions, including the possibility to study muscle function (65)(66)(67)(68)(69). 8 days after treatment, edited and control hDMD myoblasts were differentiated into a 3D hydrogel as previously described (69) (Fig 4A ; Fig S3A-B).…”
Section: Disruption Of Let-7c Bs Results In Utrophin Upregulation In ...mentioning
confidence: 99%
“…This may indicate that hiPSC-SkM-HO-1 cells affected earlier stages of muscle regeneration. Problems with the survival and/or integration of myoblasts/in vivo engraftment have been shown to limit the application of this technology (for references, see: [ 28 ]). Therefore, modifications of established protocols to increase the number of myogenic progenitors and their regenerative potential in vivo seem to be crucial for a successful therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the overexpression of Pax7 transcription factor [ 29 ] or the inhibition of p38 signaling pathway in vitro during mSC expansion enhances the cell potential to engraft in vivo [ 30 ]. A recent study by Choi et al [ 28 ] suggested modulation of NOTCH and PDGF signalling as a way to increase the migration of hiPSC-derived muscle cells for more efficient muscle cell therapies. The absence of hiPSC-derived myoblasts in murine muscle tissue may be affected by the number of injected cells, their (immature) properties, or the timing of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to assess if a fraction of the Pax7 + cells in iSMCs exit the cell cycle and return to quiescence, as previously reported for SCs seeded on myofibers [56][57][58] . Additionally, it will be of interest to assess whether serum withdrawal or modulation of additional signaling pathways might confer quiescence rather than activation on the Pax7 + cell population in iSMCs, rendering them more similar to muscle tissue during homeostasis 57,59,60 .…”
Section: Discussionmentioning
confidence: 99%